Mathematical modeling and optimal control analysis of the monkeypox Clade II infection dynamics under the recent cases of USA - Meetei, Mutum Zico; DarAssi, Mahmoud H.; Ahmad, Irfan; Khan, Muhammad Altaf; Mat Isa, Nurulfiza; Alzahrani, Ebraheem (Elsevier Ltd, 2025)
This work presents a mathematical model with optimal control analysis of the monkeypox (mpox) Clade II dynamics, particularly in response to the recent cases reported in the USA. Initially, we develop the model and outline its key properties. We identify the equilibrium points associated with the Clade II model and analyze their asymptotic stability, demonstrating that the Clade II system is locally asymptotically stable (LAS) when the threshold quantity is less than one. We derive the endemic equilibrium point and examine its corresponding results. Considering the reported cases of Clade II in the USA, we employ a nonlinear least-squares curve-fitting method to estimate the parameters. The estimated basic reproduction number, R0, is 3.3282. We conduct a global sensitivity analysis to determine the parameters that most significantly affect the threshold quantity. Furthermore, we formulate an optimal control system for the Clade II virus by introducing controls such as personal protection, treatment of infected individuals, hospital care improvement, and protection from animals (e.g., animal culling). Numerical simulations are carried out for the sensitive parameters. We also simulate both the controlled and uncontrolled systems and discuss the outcomes. The results show that implementing all control measures simultaneously leads to a more significant reduction in the number of infected cases.